The postmodern everyday life and the incidence of stroke in young adults: a descriptive-exploratory study - Juliana Vieira Fernandes; Cristiane Alves; Roberta de Freitas; Alacoque Lorenzini Erdmann; Rosane Gonçalves Nitschke; Magda Santos Koerich (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
We sought to understand the everyday life of people who had suffered from Stroke, relating it with the contemporary nuances, in younger than 45 years, in a public hospital from Florianópolis, Brazil. This is a qualitative, exploratory-descriptive study. Data were collected through recorded interviews, that were transcripted and analyzed according to Bardin's method. The following categories emerged: Way of Life; Meaning Life; Rethinking Before, Here-and-Now, and Afterwards. The results pointed-out that the contemporary way of life contributes for the prevalence of cerebrovascular diseases in younger ages. It was noticed that the majority of causes of Stroke in young adults is prevented, emphasizing the importance of measures for health promotion and prevention of illnesses. We stand out for the necessity of rethinking how nursing can contribute for the prevention of health aggravations due to contemporary way of life, promoting a more healthful life